Microgroove : Forays into Other Music - Corbett, John, 1963- (Book collections on Project MUSE., 2015)
Microgroove continues John Corbett's exploration of diverse musics, with essays, interviews, and musician profiles that focus on jazz, improvised music, contemporary classical, rock, folk, blues, post-punk, and cartoon music. Corbett's approach to writing is as polymorphous as the music, ranging from oral history and journalistic portraiture to deeply engaged cultural critique. Corbett advocates for the relevance of "little" music, which despite its smaller audience is of enormous cultural significance. He writes on musicians as varied as Sun Ra, PJ Harvey, Koko Taylor, Steve Lacy, and Helmut Lachenmann. Among other topics, he discusses recording formats; the relationship between music and visual art, dance, and poetry; and, with Terri Kapsalis, the role of female orgasm sounds in contemporary popular music. Above all, Corbett privileges the importance of improvisation; he insists on the need to pay close attention to "other" music and celebrates its ability to open up pathways to new ideas, fresh modes of expression, and unforeseen ways of knowing --